2011
DOI: 10.1074/jbc.m111.241000
|View full text |Cite
|
Sign up to set email alerts
|

STR-33, a Novel G Protein-coupled Receptor That Regulates Locomotion and Egg Laying in Caenorhabditis elegans

Abstract: Despite their predicted functional importance, most G protein-coupled receptors (GPCRs) in Caenorhabditis elegans have remained largely uncharacterized. Here, we focused on one GPCR, STR-33, encoded by the str-33 gene, which was discovered through a ligand-based screening procedure. To characterize STR-33 function, we performed UV-trimethylpsolaren mutagenesis and isolated an str-33-null mutant. The resulting mutant showed hypersinusoidal movement and a hyperactive egg-laying phenotype. Two types of egg laying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Since the tph-1 mutant is known to exhibit abnormality in food sensation and ingestion in C. elegans, we sought to confirm that R02D3.7 is not expressed in serotonergic neurons. To this end, we constructed transgenic lines that co-expressed R02D3.7::mCherry and tph-1::GFP from their native promoters and examined overlap [26,27]. Our analysis confirmed that R02D3.7 and tph-1 are expressed in different neuronal cells (Figure 2B).…”
Section: R02d37 Is Expressed In Dopaminergic Neuronsmentioning
confidence: 57%
See 1 more Smart Citation
“…Since the tph-1 mutant is known to exhibit abnormality in food sensation and ingestion in C. elegans, we sought to confirm that R02D3.7 is not expressed in serotonergic neurons. To this end, we constructed transgenic lines that co-expressed R02D3.7::mCherry and tph-1::GFP from their native promoters and examined overlap [26,27]. Our analysis confirmed that R02D3.7 and tph-1 are expressed in different neuronal cells (Figure 2B).…”
Section: R02d37 Is Expressed In Dopaminergic Neuronsmentioning
confidence: 57%
“…Regarding the dopaminergic neuron-specific expression of rcat-1, previous studies of the effects of serotonin on locomotion during food searching [5,46] and our results from serotonin biosynthesis mutants do not support a serotonergic signaling pattern (Figure 2B). In fact, tph-1(mg280), a TH mutant [27], exhibited no change in food-search behavior (Figure 2C). Taken together, our findings indicate that rcat-1 may be involved in the negative feedback regulation of dopamine metabolism (synthesis and release) in a cell type-specific manner (dopaminergic neurons).…”
Section: Discussionmentioning
confidence: 99%
“…We find that metformin significantly improves fecundity in worms that express Aβ (Figure 7.3). As ACh and serotonin signaling both modulate egg laying behaviour in C. elegans [579][580][581][582][583][584], it is entirely possible that the improvement in fecundity and egg viability by metformin results from improved function of these signaling systems. The metformin mediated increase in fecundity reflects a decrease in Aβ-mediated toxicity in adults, whereas the improved egg viability probably reflects a decrease in Aβ toxicity at the embryonic stage of development.…”
Section: Discussionmentioning
confidence: 99%